Pengaruh Aplikasi Telehomecare terhadap Pengetahuan Penderita Tuberculosis Paru tentang Penularan Penyakit Tuberculosis - Ning Arti Wulandari (Journal of Ners and Midwifery, 2017)
Tuberculosis (TB) disease is transmitted through a "droplet infection". Currently it is still very difficult to cut the chain chain of transmission of tuberculosis disease, this is due to lack of knowledge of patients about the prevention of transmission of tuberculosis. Forms of health services to patients with tuberculosis currently focuses on treatment. Education is actually also given but still less than the maximum due to limited time to have a health officer reach too broad. Therefore the use of technology in providing nursing care to tuberculosis patients at home. The technique used is telehomecare, where officers will provide education and followup to tuberculosis patients through cellular telepone. The purpose of this study was to identify the effect of telehomecare application on the knowledge of pulmonary tuberculosis patients about Tuberculosis disease transmission. Method: The design of this study was one group pretest posttest design, conducted from 18 April to 30 June 2012 with a sample of 14 pulmonary tuberculosis patients in the work area of Puskesmas Kanigoro Blitar district taken from the entire population. The data obtained will be analyzed with Wilcoxon Signed Rank test. The results of this study there are differences in knowledge before and after being given education via telehomecare with a value of P = 0.02. Discussion: Telehomecare program can be applied in Puskesmas, clinic or hospital to improve nursing care service